2016
DOI: 10.1590/s0104-12902016153819
|View full text |Cite
|
Sign up to set email alerts
|

Análise das demandas judiciais para aquisição de medicamentos no estado da Paraíba

Abstract: This study aimed to describe the medical, scientific, and sanitary aspects of lawsuits for drug supply filed with the Court of Paraíba (TJ-PB) against public officials in the state of Paraíba, Brazil. It was a descriptive and cross-sectional study, which had as source the Information System of the Paraíba Court. Drug processes judged at the second instance between the years 2009 and 2010 with a final decision already made at the time of consultation were analyzed. About the scientific evidences of efficacy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 5 publications
1
9
0
10
Order By: Relevance
“…The system's logic is to plan coverage based on epidemiological criteria, and these responsibilities are defined in ministerial ordinances. Similar result was found by Nunes and Ramos Junior (2016), in which 84.7% of the lawsuits were filed against the state department (the study included the Federal government), and by Leitão et al (2016), in which 79.3% of the lawsuits were filed against the state. The legal representation, for the most part, comes from assistance agencies to people who declare themselves unable to afford judicial costs, such as the Federal Public Defender's Office, State Public Defender's Office, Public Prosecution Office and Federal Prosecution Office, which corresponds to 75.47% of the suits.…”
Section: Graph 1 -Lawsuits Filed Against the Municipal Health Departmsupporting
confidence: 85%
See 4 more Smart Citations
“…The system's logic is to plan coverage based on epidemiological criteria, and these responsibilities are defined in ministerial ordinances. Similar result was found by Nunes and Ramos Junior (2016), in which 84.7% of the lawsuits were filed against the state department (the study included the Federal government), and by Leitão et al (2016), in which 79.3% of the lawsuits were filed against the state. The legal representation, for the most part, comes from assistance agencies to people who declare themselves unable to afford judicial costs, such as the Federal Public Defender's Office, State Public Defender's Office, Public Prosecution Office and Federal Prosecution Office, which corresponds to 75.47% of the suits.…”
Section: Graph 1 -Lawsuits Filed Against the Municipal Health Departmsupporting
confidence: 85%
“…The study of Pinto and Osório-de-Castro (2015) also highlights that most of the actions were filed by public defenders (62%). There is divergence with the studies of Vieira and Zucchi (2007), Nunes and Ramos Junior (2016), Leitão et al (2016) and Machado et al (2011), in which the number of representations made by private lawyers prevailed (54%, 68.4%, 55.17% and 60.3%, respectively). The study by Nunes and Ramos Junior (2016) found greater use of the judicialization strategy in upper classes.…”
Section: Graph 1 -Lawsuits Filed Against the Municipal Health Departmmentioning
confidence: 62%
See 3 more Smart Citations